Performance Simulation of Sino-Tibetan Temple Spatial Layouts: Modern Application of Traditional Construction Approaches - Nan Jiang; Dawei Shang; Ya Tuo (Buildings)
During their evolution, Sino-Tibetan temples have been influenced by multiple factors, including history, geography, and climate, resulting in a variety of distinctive spatial layouts. Through performance simulations, many traditional construction methods have been found to still offer valuable insights for contemporary architectural designs. This study selects several typical spatial layouts that emerged during the evolutionary process as research subjects and uses the building simulation software (Ladybug Tools 1.7.0) for simulation. Comparative analysis of the thermal and wind environment simulation results reveals that the layout with directly connected front and rear spaces offers a 10% higher ventilation efficiency than the courtyard-inserted layout. Although the wind field is relatively uniform, excessive influx of hot air disrupts the indoor thermal environment. When a buffer space is introduced as a transition, ventilation efficiency decreases by approximately 12%, but indoor dissatisfaction decreases by an average of 3%. The central courtyard and direct separation layouts enhance ventilation by altering the wind pressure difference between the indoor and outdoor environments. Under conditions of weak wind, indoor comfort satisfaction remains stable between 75% and 78%. This study re-examines the spatial forms of Sino-Tibetan temples, analyzing the pros and cons of various spatial layouts from the perspective of architectural performance and proposing strategies for their application in modern design. Furthermore, the conclusions of this research contribute to the future protection or renovation of these temples without compromising the original architectural concept.